The World Health Organization's work and recommendations for improving the health of trans and gender diverse people. (12th October 2022) - Macdonald, Virginia; Verster, Annette; Mello, Maeve B.; Blondeel, Karel; Amin, Avni; Luhmann, Niklas; Baggaley, Rachel; Doherty, Meg
Abstract: Introduction: The World Health Organization (WHO) is guided by its global programme of work and the goal that a billion more people have universal health coverage (UHC). To achieve UHC, access for those most vulnerable must be guaranteed and prioritized. WHO is committed to developing evidence‐based guidance to work towards UHC for trans and gender diverse (TGD) people. This commentary describes WHO's work related to TGD people over the last decade. Discussion: In 2011, WHO developed guidelines for the prevention and treatment of HIV and sexually transmitted infections (STIs) in men who have sex with men and TGD people. In 2013, the "HIV civil society reference group" called on WHO to provide specific guidance for TGD people. Values and preferences of TGD people were considered by WHO for the first time, which informed the development of the 2014 WHO Consolidated Guidelines on HIV Prevention, Diagnosis, Treatment and Care for Key Populations. The 2014 Guidelines included a comprehensive package of HIV‐related health and enabling interventions with specific considerations for TGD people, as well as a specific policy brief in 2015. Regional WHO offices developed and/or supported the development of blueprints on transgender health and HIV in 2014 and 2016. A 2015 WHO report on sexual health, human rights and the law elucidated the harmful impacts of discriminatory laws on the basis of sexual orientation and gender identity. In 2019, the 11th edition of the international classification of diseases saw the removal of "transsexualism" as a mental and behavioural disorder. WHO's first guideline on self‐care interventions, updated in 2021, included key considerations concerning TGD people. In 2022, WHO's updated key populations guidelines include a prioritized package of not just HIV, but also viral hepatitis and STI health interventions for TGD people. Still, a broader and more specific health approach and a greater focus on social issues are needed to better serve the health needs of TGD people. Conclusions: WHO's understanding and commitment to TGD people's health has evolved and improved over the past decade. Together with professional and community trans health organizations, WHO should now start developing evidence‐informed global guidance on TGD health as part of its remit to support UHC to all.